2021
DOI: 10.3390/jcm10173882
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging Biomarkers for Clinical Impairment and Disease Progression in Patients with Shoulder Adhesive Capsulitis: A Prospective Study

Abstract: Background: MRI diagnostic criteria of shoulder adhesive capsulitis (AC) are nowadays widely used, but there is little information available on the association between MRI findings and clinical impairment. Purpose: To determine the correlation of MRI findings with the Constant–Murley Score (CMS), pain duration and symptoms at the one-year follow-up in AC patients. Materials and methods: This monocentric prospective study included 132 patients with a clinical diagnosis of shoulder AC who underwent shoulder MRI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 45 publications
0
2
0
1
Order By: Relevance
“…Therefore, it is difficult to interpret that the MRI scan exactly represents the patient’s stiffness. However, as stiffness does not usually resolve in a short period, 8 the effect would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is difficult to interpret that the MRI scan exactly represents the patient’s stiffness. However, as stiffness does not usually resolve in a short period, 8 the effect would not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus on the use of the increase in signal intensity of the joint capsule at the axillary recess level in the diagnosis of adhesive capsulitis since the evaluation of this increase often varies from person to person. In a prospective study by Gillet et al, 17 in which the relationship between MRI findings and clinical examination findings was investigated in patients with adhesive capsulitis, joint capsule thicknesses of the patients were measured at the axillary recess level, and the signal intensities of the joint capsule thereof were graded using 4 different grade levels. Consequentially, it was found that the pain and mobility scores, which are the clinical criteria investigated within the scope of the study, were found to have differed between the low and high signal intensity groups ( P < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Gillet et al 67 , em 2021, publicam estudo em que são avaliadas RM de achados compatíveis com a doença na RM são correlacionados com dados clínicos e com a evolução em relação à dor. As RM são avaliadas por dois radiologistas com 3 e 7 anos de experiência e os parâmetros documentados incluem: presença de hipersinal do ligamento glenoumeral inferior, espessura da cápsula no recesso axilar (porção umeral e glenoidal) e espessura do ligamento coracoumeral.…”
Section: Ressonância Magnética Com Contrasteunclassified